Biofilm producing multidrug resistant Acinetobacter species from a tertiary care hospital: a therapeutic challenge - Bala, Manju; Gupte, Satish; Aggarwal, Prerna; Kaur, Maninder; Manhas, Ashwini (International Journal of Research in Medical Sciences, 2017)
Background: Acinetobacter species are responsible for nosocomial infections which are related to the biofilm forming capacity of this pathogen. Biofilm formation helps the bacteria in surviving stressed environmental conditions and bacteria growing in biofilms are multidrug resistant. The objective was to detect biofilm formation and its relation to drug resistance among Acinetobacter spp isolates. Methods: A total of 75 clinical isolates of Acinetobacter species were tested for biofilm production by microtitre plate method and susceptibility to antibiotic discs were determined by Kirby Bayer Method. Results: On testing by tissue culture plate method, 12 (16%) Acinetobacter isolates were weak biofilm producers, 9 (12%) were moderate producers, 30 (40%) were strong biofilm producers, 24 (32%) isolates were nonbiofilm producers and 63 % isolates were multidrug resistant. Conclusions: This study demonstrates the ability of Acinetobacter isolates to form biofilm and biofilm production has strong association with multiple drug resistance.